Plant-Soil Feedbacks of Plantago lanceolata in the Field Depend on Plant Origin and Herbivory - Kirchhoff, Leah; Kirschbaum, Anna; Joshi, Jasmin; Bossdorf, Oliver; Scheepens, J. F.; Heinze, Johannes (Frontiers in Ecology and Evolution, 2019)
Soil biota involved in plant-soil feedbacks (PSFs) have an impact on the growth of plant individuals. So far, studies investigating the role of soil-biota mediated PSFs in plant performance were mostly performed in greenhouses and focused predominantly on species differences, whereas the contribution of PSFs to plant performance under field conditions and intraspecific variation in PSFs among plant populations remain poorly investigated. Here, we performed a PSF pot experiment under field conditions to study intraspecific variation in plant responses to soil biota. We used seeds from multiple seed families of Plantago lanceolata L. together with Plantago-conditioned soils from contrasting habitats (three non-fertilized pastures vs. three fertilized mown pastures) to test whether plants show a positive or negative response to their parental soil biota. We furthermore tested whether these PSFs depend on microclimate and insect herbivory. To this end, we reciprocally transplanted plants and their soil biota between the two habitat types and excluded aboveground herbivores from half of the plants, respectively. When grown without herbivores, plants from both habitat types showed similar and neutral PSFs independently of the transplant site. In contrast, in the presence of herbivores, PSFs for plants from non-fertilized pastures were negative in both habitats (i.e. plants performed better when they grew with foreign soil biota), whereas PSFs for plants from fertilized mown-pastures remained neutral. Our results suggest that soil biota alone might only play a minor role for performance of P. lanceolata and that the outcome of soil-biota mediated PSFs is modulated by effects of herbivores in different habitats.